The influence of conventional non-surgical periodontal treatment in glycemic control of patients diagnosed with diabetes mellitus and periodontitis - review of literature - Rodrigues, Maria Mikaele Mota (2019)
Objective: to review the literature on the influence of conventional non-surgical periodontal treatment (CPT) in terms of glycemic control in diabetic patients diagnosed with periodontitis. Material and Methods: we used the descriptors Diabetes mellitus, Periodontitis and Therapy, in English, to search the PubMed database, from 2015 to 2019. A total of 233 articles were found, and after reading all abstracts, we selected 25 related to the subject and fully read them. Literature reviews, in vivo research and clinical trials without systemic analysis of patients, especially regarding glycemic tests, or aimed at evaluating drug effects, were excluded. Results: most of the selected clinical trials prospectively analyzed the present association. Twenty studies indicated the CPT may positively influence in glycemic control in patients diagnosed with DM and periodontitis. Proinflammatory cytokines are known to increase peripheral cellular resistance to insulin action and to have a causal relationship with DM. The present result was associated with the potential of CPT, performed through supra and subgingival scraping, to reduce the local microbial load and, consequently, the massive concentration of inflammatory mediators in the free gingival groove or periodontal pocket, reducing their spread. Conclusion: CPT has systemic benefits by facilitating glycemic control in patients with diabetes. It is suggested the visits to the dentist should be recorded in the treatment of diabetic patients